PERSEPSI PETANI TENTANG PENGEMBANGAN AGROWISATA BERBASIS PADI DAN FAKTOR YANG MEMPENGARUHINYA DI KECAMATAN BUNGA RAYA KABUPATEN SIAK PROVINSI RIAU - Jamalludin; Noer, Melinda; Syahni, Rahmat; Nofialdi (JURNAL AGRICA, 2025)
Rice field agro-tourism is a tourist destination that carries the concept of nature by utilizing agricultural land to provide education about the agricultural sector. The purpose of the study was to analyze the perceptions of rice paddy farmers towards the development of rice-based agro-tourism, and the factors that influence it. In this study, respondents consisted of a sample of rice paddy farmers. With a population of 2,106 rice farmers, and a sample of 92 farmers. Analysis used Likert scale and multiple regression analysis. The results of the analysis show the perception of rice paddy farmers on the development of agro-tourism based on rice paddy in Bunga Raya District, Siak Regency, it is known that all rice paddy farmers agree, developed, as long as the development continues to pay attention to the preservation of environmental functions, preservation of natural potential and preservation of socio-cultural values of the community. Variables used based on findings affect the level of development of agro-tourism based on rice paddies, variables that have a very real effect are: the benefits of rice-based agro-tourism development, the development of home industry, the existence of agricultural land, the participation of the community of rice paddy farmers and employment opportunities for the community of rice paddy farmers, levy collection. While the variable that does not have a very real effect is the income of the community of rice paddy farmers.